PENGARUH PENGGUNAAN MEDIA RODA BACA TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS I DI SD NO. 2 DALUNG TAHUN PELAJARAN 2025/2026 - Listia Manik, Ni Luh Putri; I Gusti Ngurah Triyana; I Made Sukariawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The focus of this research is motivated by the low reading literacy skills of first-grade students at SD No. 2 Dalung. Based on field observations, a phenomenon was discovered where most students still face obstacles in distinguishing similar letter shapes, experience difficulty pronouncing consonantvowel combinations, and show low enthusiasm toward conventional learning media. The objective of this quantitative research, which employs a Quasi-Experimental design, is to determine the effectiveness of "Roda Baca" as a learning tool for reading. The participants consisted of 56 first-grade students at SD No. 2 Dalung, divided into a control group and an experimental group. Data were collected through observation, documentation, and pre-test and post-test assessments. The data were analyzed using the Independent Samples T-Test with the assistance of IBM SPSS Statistics 23.Data collection techniques included observation, documentation, and pretest and post-test instruments.  The collected data were analyzed using the Independent Sample T-Test via IBM SPSS Statistics 23 software.